2020
DOI: 10.1093/jalm/jfaa072
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Domain I β2-Glycoprotein I Antibodies and Activated Protein C Resistance Predict Thrombosis in Antiphospholipid Syndrome: TAC(I)T Study

Abstract: Background Antibodies binding to domain I of β2-glycoprotein I (aDI) and activated protein C (APC) resistance are associated with an increased risk of thrombosis in cross-sectional studies. The objective of this study was to assess their predictive value for future thromboembolic events in patients with antiphospholipid antibodies (aPL) or antiphospholipid syndrome. Methods This prospective multicenter cohort study included c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
0
25
0
2
Order By: Relevance
“…Some studies have shown that aPC resistance is associated with thrombotic events in patients with APS. [31][32][33] aPC resistance is thought to be one of the ways through which LA is associated with a pro-thrombotic phenotype in APS. 17,19 Fluorogenic thrombin generation measurements have shown that the presence of LA is associated with a decreased aPC-induced inhibition of the ETP and peak thrombin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that aPC resistance is associated with thrombotic events in patients with APS. [31][32][33] aPC resistance is thought to be one of the ways through which LA is associated with a pro-thrombotic phenotype in APS. 17,19 Fluorogenic thrombin generation measurements have shown that the presence of LA is associated with a decreased aPC-induced inhibition of the ETP and peak thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that aPC resistance is associated with thrombotic events in patients with APS 31‐33 . aPC resistance is thought to be one of the ways through which LA is associated with a pro‐thrombotic phenotype in APS 17,19 .…”
Section: Discussionmentioning
confidence: 99%
“…62 Furthermore, depending on the research question, reference ranges can be measured on a specific patient population (e.g., APS patients) for appropriate between-group comparisons. 63 In other applications of TG, such as monitoring of antithrombotic drugs and assessment of bleeding and thrombotic risk levels of TG, TG parameters are compared between patient groups. 5,64,65 Each study should report what reference ranges they applied for interpretation of results.…”
Section: Reference Valuesmentioning
confidence: 99%
“…These reference ranges may be acceptable if local measurements of 20 or more healthy subjects yield comparable results 62 . Furthermore, depending on the research question, reference ranges can be measured on a specific patient population (e.g., APS patients) for appropriate between‐group comparisons 63 . In other applications of TG, such as monitoring of antithrombotic drugs and assessment of bleeding and thrombotic risk levels of TG, TG parameters are compared between patient groups 5,64,65 .…”
Section: Analytical and Post‐analytical Factorsmentioning
confidence: 99%
“…Indeed, 2 prospective studies identified in this review looked specifically at the clinical relevance of anti-B2GPI D1 positivity and reported a significant association with rates of thrombosis. 49,50 Further progress to standardize anti-B2GPI D1 testing and, ultimately, to clarify its clinical relevance is needed.…”
Section: Relationship Between Igg Anti-b2gpi Positivity and Aps Obstetric Clinical Manifestationsmentioning
confidence: 99%